HUBUNGAN ANTARA PRAKTIK RANTAI PASOKAN, RANTAI PERMINTAAN, KEUNGGULAN KOMPETITIF DAN KINERJA PERUSAHAAN: STUDI PADA PERUSAHAAN-PERUSAHAAN KONSTRUKSI DI KOTA TARAKAN (KALTIM) - , Hariyadi Hamid, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to analyze the relationship between supply chain practices, demand chain practices, competitive advantage and company performance. This study also aims to examine the mediating impact of competitive advantage of the relationship of supply chain practices and demand chain practices with both financial and non-financial performance. There are 143 respondents in this research which are construction companies in Tarakan City (East Borneo). Data was collected by survey through distributing questionnaires. The hypothesis in are examined by using Structural Equation Modeling (SEM). The result of this study shows that the supply chain practices and the demand chain practices has significant positive relationship with the competitive advantage. Although the competitive advantage has effect with company performance, both non-financial performance, and financial performance, the supply chain practices has direct effect to non-financial performance, but the supply chain practices has negative impact on financial performance. In addition, demand chain practice does not have impact on non-financial performance and negative impact on the companyâs financial performance. The competitive advantage does not have mediating impact in supply chain practices towards nonfinancial performance, and the competitive advantage does have mediating impact in supply chain practices towards financial performance. The competitive advantage does have mediating impact in demand chain practices towards company performance, both non-financial performance and financial performance. The result of this study is also shows that the non-financial performance has direct impact with financial performance.